TOPICAL IMMUNOTROPIC AGENTS IN TREATMENT - V.A. Bulgakova; I.I. Balabolkin; T.B. Sentsova; L.K. Katosova; I.V. Ryleeva; N.V. Yukhtina; N.V. Bashilova (Педиатрическая фармакология)
Of intercurrent infections in children with allergic pathology use of topical bacterial lyzates as a therapy for intercurrent infections in children with allergic pathology is reviewed basing on publications and personal clinical experience. Deficient mucous immunity has been established in allergic children with recurrent and acute upper respiratory tract and herpes virus infections, thus providing base for use of immunomodulators as a part of complex treatment for this group of patients.Key words: children, allergic diseases, respiratory tract infections, stomatitis, prophylaxis, treatment, immunomodulators.